Different Age-Induced Changes in Rhizosphere Microbial Composition and Function of Panax ginseng in Transplantation Mode - Wang, Qiuxia; Sun, Hai; Li, Meijia; Xu, Chenglu; Zhang, Yayu (Frontiers in Plant Science, 2020)
Transplantation is a cultivation mode widely applied in perennial plant growing. This method might be an effective way to alleviate problems associated with continuous cultivation (4-6 years) in ginseng production, but the alleviating mechanism and effects on soil microbial community is unclear. To study this issue, non-transplanted two-year-old, and five-year-old (transplantation mode: 2+3) and nine-year-old (transplantation mode: 3+3+3) ginseng rhizosphere soils were analyzed via MiSeq sequencing. The results showed that nine-year-old ginseng rhizosphere soil had lower available nitrogen and the lowest pH, available phosphorus, observed species and community diversity and richness (Chao1, and ACE) among all samples (P<0.05). The abundances of some bacterial classes (Thermoleophilia, Bacilli, and Nitrospira) and fungal genera (Mortierella, Epicoccum, and Penicillium spp.) and functional richness associated with nutrient element cycles and antifungal activity decreased, while abundances of some fungal genera (Ilyonectria, Tetracladium, and Leptodontidium spp.) increased with increasing age of ginseng plants (P<0.05 or P<0.01). However, there was greater similarity between soil samples of two-year-old and transplanted five-year-old ginseng plants and the increase in cultivation time from two to five years did not significantly influence the microbial community, suggesting that transplantation is a viable strategy for suppressing soil-borne diseases in P. ginseng plants over long growth periods.